Amplification of gravitationally induced entanglement - Feng, T; Vedral, V (American Physical Society, 2022)
Observation of gravitationally induced entanglement between two massive particles can be viewed as implying the existence of the nonclassical nature of gravity. However, weak interaction in the gravitational field is extremely small so that gravitationally induced entanglement is exceptionally challenging to test in practice. For addressing this key challenge, here we propose a criterion based on the logical contradictions of weak entanglement, which may boost the sensitivity of the signal due to the gravitationally induced entanglement. Specifically, we make use of the weak-value scenario and Einstein-Podolsky-Rosen steering. We prove that it is impossible for a classical mediator to act on two local quantum objects to simulate amplified-weak-value phenomenon in two-setting Einstein-Podolsky-Rosen steering. Our approach can amplify the signal of gravitationally induced entanglement that were previously impossible to observe by any desired factor that depends on the magnitude of the weak value. Our results not only open up the possibility of exploring nonclassical nature of gravity in the near future, but they also pave the way for weak entanglement criterion of a more general nature.